2010
DOI: 10.1080/00103620903494376
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Buffer Solutions for Determining the Lime Requirement for Ohio Soils

Abstract: Lime is used as a soil amendment to achieve the optimum pH suitable for good crop growth. Buffer pH (BpH) measurements have been calibrated to relate the linear drop in pH of the soil-buffer system to the amount of lime needed to neutralize soil to a certain pH level. The amount of lime required to neutralize soil acidity, called the lime requirement (LR), is obtained from soil-limestone (CaCO 3 ) incubations. In this study, 13 soils from Ohio were incubated with CaCO 3 for a period of 1 month to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nonhazardous buffer pH methods have been calibrated using lime incubation studies in various regions and have been shown to be effective alternatives to hazardous methods. Based on correlation to incubation lime requirement, the Sikora method was shown to be accurate for estimating lime requirement in Ohio (Viswakumar et al., 2010), Brazil (Santanna et al., 2011), and Missouri (Nathan et al., 2012), with r 2 = .40–.73, .97, and .73–.82 respectively. Similarly, the modified Mehlich method was shown to be an accurate LRE method in Maine (Hoskins & Erich, 2008), Missouri (Nathan et al., 2012), and eastern Washington (McFarland et al., 2020), with r 2 = .91–.96, .82–.89, and .90 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nonhazardous buffer pH methods have been calibrated using lime incubation studies in various regions and have been shown to be effective alternatives to hazardous methods. Based on correlation to incubation lime requirement, the Sikora method was shown to be accurate for estimating lime requirement in Ohio (Viswakumar et al., 2010), Brazil (Santanna et al., 2011), and Missouri (Nathan et al., 2012), with r 2 = .40–.73, .97, and .73–.82 respectively. Similarly, the modified Mehlich method was shown to be an accurate LRE method in Maine (Hoskins & Erich, 2008), Missouri (Nathan et al., 2012), and eastern Washington (McFarland et al., 2020), with r 2 = .91–.96, .82–.89, and .90 respectively.…”
Section: Introductionmentioning
confidence: 99%